STRATEGI PENGEMBANGAN WISATA PANTAI DALAM PENINGKATAN PENDAPATAN EKONOMI MASYARAKAT PESISIR DI KABUPATEN BONE BOLANGO - Muhammad Yusuf Zulfkar Paudi; Frahmawati Bumulo; Sri Indriyani S. Dai (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2022)
This study aims to find out how the beach tourism development strategy is in increasing the economic income of coastal communities in Bone Bolango Regency. This research uses a quantitative approach with descriptive methods. The sample in this study were 30 people. Collecting data using questionnaires and interviews. The data analysis technique uses SWOT analysis.The research results show that the position of the beach tourism development strategy in increasing the economic income of coastal communities in Bone Bolango Regency is currently in quadrant 2, namely diversification strategy. This strategy emphasizes that the government of Bone Bolango Regency must be able to optimize various coastal tourism potentials to reduce threats supported by efforts to increase opportunities for cooperation, collaboration, and budget support. The strategic steps that can be taken are (1) Integrating the potential for beach tourism with the creative economy handicraft products of the community so that the community's household economy can move to increase higher incomes and better recognition of the image of the regional characteristics of Bone Bolango Regency. (2) Equity participation by the government in the formation of regional-owned enterprises for the management of beach tourism in collaboration with local BUMDes and budget allocations for adequate and conducive accessibility. (3) Increasing the capacity of the community to be more innovative in beach tourism institutions and partnerships so that the community can further develop security, comfort and other positive things related to beach tourism.